ECONOMIC VALUATION ON LONGWALL COAL MINING PROJECT OF PT. XYZ USING REAL OPTION METHOD - Chandra Bahari, Ekiko
In general, mining investment analysis calculations use discounted cash flow method because it is relatively easy. However, the method does not pay attention to the uncertainty factor. Economic uncertainty factors on coal mining projects can be quantitatively calculated using Binomial Lattice and Rainbow Options. Based on the calculation result, obtained NPV value using Discounted Cash Flow method of $(88,172,629.09). Then , used 2 parameters of uncertainty such as the historical value of commodity prices and us inflation rate. Lattice parameters: Underlying Asset volatility of commodity prices (?2)=64.12%, Underlying Asset Volatility from Inflation (?2)=38.05%, Risk Free Rate (r)=6.83%, Principal Asset Value (S)= $17,582,818.81 , Capital Cost (K)= $105,755,447.90. Then it obtained an Option Value of $4,823,590.22 with coal price as Uncertainty. $1,041,453.82 with Inflation as Uncertainty. $17,902,890.71 with Rainbow Option. The results of sensitivity analysis show that Selling Price is the most sensitive parameter to npv value change.